Chitosan-based thermosensitive composite hydrogel enhances the therapeutic efficacy of human umbilical cord MSC in TBI rat model. (December 2019) - Yao, M.; Chen, Y.; Zhang, J.; Gao, F.; Ma, S.; Guan, F.
Abstract: Recently, stem cell–based therapy shows great promise in treating traumatic brain injury. However, the low rate of cell engraftment and survival are two major barriers for efficacy. To improve the therapeutic effect, a new thermosensitive hydrogel based on chitosan, hydroxyethyl cellulose, hyaluronic acid, and β-glycerophosphate (CS-HEC-HA/GP) was developed in this study. This CS-HEC-HA/GP hydrogel exhibits a faster gelation process and better biocompatibility to human umbilical cord mesenchymal stem cells (hUC-MSC) versus CS/GP or CS-HEC/GP hydrogels. The suitable rheological behavior similar to brain tissue supports that the CS-HEC-HA/GP hydrogel might be a preferable neural scaffold. In addition, CS-HEC-HA/GP hydrogel loaded with hUC-MSC could enhance the retention, survival, and migration of encapsulated hUC-MSC, improve survival and proliferation of endogenous neural cells probably by secreting neurotrophic factors and inhibiting apoptosis, and thereby accelerate remodeling of brain structure and neurological function recovery in TBI rats. Thus, this hydrogel shows enormous potentials in stem cell–based neural tissue repair and regeneration. Highlights: A new thermosensitive hydrogel based on chitosan, hydroxyethyl cellulose, hyaluronic acid, and β-glycerophosphate (CS-HEC-HA/GP) is developed. This hydrogel possesses fast gelation rate and good biocompatibility. CS-HEC-HA/GP hydrogel enhances the retention and migration ratio of injected human umbilical cord mesenchymal stem cells (hUC-MSC). CS-HEC-HA/GP hydrogel loaded with hUC-MSC could accelerate the brain trauma healing and promote the neurological function recovery of traumatic brain injury model in rats.